Knowledge Sharing and Learning Culture in Driving Employee Innovation Through Adaptive Competence as a Mediating Variable - I Gusti Ngurah Widya Hadi Saputra; I Gusti Ayu Ratih Swandewi; Nilna Muna; Ni Putu Nina Eka Lestari (Journal of Innovative and Creativity, 2025)
Public sector organizations are increasingly required to be adaptive, collaborative, and innovative in responding to technological advancements and the growing complexity of societal needs. This study aims to examine the role of knowledge sharing and learning culture in enhancing employee innovation, with adaptive competence as a mediating variable at the Badan Pendapatan Daerah (Bapenda) of Badung Regency. A quantitative approach was employed using a saturated sampling technique involving all 378 employees. Data were collected through a Likert-scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results reveal that knowledge sharing has a positive and significant effect on employee innovation, indicating that stronger knowledge-sharing practices lead to greater innovative behavior. Learning culture positively and significantly influences employee innovation, indicating that a supportive learning environment enhances employees’ innovative capacity. Knowledge sharing also strengthens adaptive competence, while a learning culture similarly improves employees’ adaptability. Adaptive competence itself has a significant positive effect on employee innovation, showing that more adaptable employees tend to be more innovative. Mediation results confirm that adaptive competence partially mediates the effects of both knowledge sharing and learning culture on employee innovation. Thus, these factors enhance innovation not only directly but also indirectly through improved adaptive capabilities. These findings highlight the strategic importance of strengthening learning culture, facilitating knowledge sharing, and enhancing adaptive competence as key enablers of employee innovation in the public sector context.